Efficient Synthesis of a 5α-Reductase Inhibitor, 3-(Tetrazol-5-yl)-3,5-pregnadien-20-one through Allylic Rearrangement of Cyanophosphates - Yoneyama, Hiroki; Usami, Yoshihide; Harusawa, Shinya (Synthesis, 2019)
We describe the use of allylic rearrangements of cyanophosphates for the efficient and practical synthesis of 3-(tetrazol-5-yl)-3,5-pregnadien-20-one, which is a potent 5α-reductase inhibitor (IC50: 15.6 nM), from pregnene-3,20-dione in 92% overall yield in four steps.
Keywords: synthesis; DEPC; cyanophosphates; allylic rearrangement; 3-(tetrazol-5-yl)-3,5-pregnadien-20-one; 5AR inhibitor